Рrevalence and structure of metabolic diseases of laying hens - Shcherbatyi, A. R.; Slivinska, L. G. (Baltija Publishing, 2022)
Metabolic diseases are the largest group of poultry diseases. They are classified as metabolic diseases, or metabolic diseases, and cause significant economic losses. Laying hens are most often diagnosed with hepatitis, hepatosis, cirrhosis, liver abscesses, cholecystitis, and gallstone disease resulting from impaired carbohydrate, lipid, protein, and mineral metabolism. Lack of calcium, Phosphorus, and vitamin D imbalance in laying hens causes osteoporosis and hypocalcemia. Due to these diseases in chickens, the laying capacity, the quality of hatching eggs, and the hatching of young animals are reduced and can cause the death of embryos and adult livestock. A lack of vitamins A, D, E, and microelements Co, Cu, Zn, and J in poultry leads to a decrease in immunity, reproductive function, laying, disruption of hormonal activity, work of internal organs and the nervous system, and cessation of growth. Hypovitaminosis and microelementosis cause the formation of rotten eggs and the development of alimentary dystrophies in the embryo, affecting the young's hatchability and quality. Therefore, improving the feeding and laying of hens standards is constantly ongoing based on an in-depth study of these processes. The purpose of this work is to conduct a comparative review of the results obtained by various authors regarding the most common metabolic diseases of laying hens, their impact on productive traits (laying), quality characteristics of eggs, embryogenesis, and quality of young of modern high-performance crosses.
Topical issues of the development of veterinary medicine and breeding technologies : scientific monograph.
Keywords: метаболічні хвороби курей-несучок; кури-несучки; metabolic diseases of laying hens; laying hens